Answers

2014-08-10T13:32:47+05:30
Ans= -35/27

3/4+5/12=14/12=7/6

divide by reciprocal is same as multiplying.
7/6 x -15/8 x 16/27 = -35/27
0
2014-08-10T13:33:09+05:30
First find the sum, \frac{3}{4} +  \frac{5}{12} =  \frac{9 + 5}{12} =  \frac{14}{12} =  \frac{7}{6}

now find the product, - \frac{15}{8} *  \frac{16}{27} = - \frac{16}{8} *  \frac{15}{27} = -2 *  \frac{5}{9} = - \frac{10}{9}

So reciprocal = - \frac{9}{10}

Now divide, \frac{ \frac{7}{6} }{- \frac{9}{10} } =  \frac{7}{6} * - \frac{10}{9} = - \frac{10}{6} *  \frac{7}{9} = - \frac{5}{3} *  \frac{7}{9} = - \frac{35}{27}

Answer
- \frac{35}{27}
0
7/6 divided by (-9/10) =7/6 x (-10/9)= -35/27
yup my mistake